2012
DOI: 10.5644/ama2006-124.46
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between difficulties in psychological adjustment in young adulthood and exposure to bullying behaviour in childhood and adolescence

Abstract: Objective. This study investigates the relationship between involvement in bullying in childhood and adolescence and psychological difficulties in young adulthood. Materials and method. A total of 249 college students completed the Retrospective Bullying Questionnaire and Trauma Symptom Checklist. Results. The results showed significant differences in psychological adjustment among respondents who were exposed to bullying compared to respondents who were not exposed to bullying. Those exposed to bullying had s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 71 publications
0
8
0
2
Order By: Relevance
“…Concerns about the prevalence of bullying are magnified by concerns about the adverse physical, social, and psychological effect on both the victims and perpetrators of bullying. There is evidence to show that bullying and victimization are strongly related to behavioral misconduct [ 13 , 14 ], poor physical health [ 15 , 16 ], psychosocial adjustment [ 17 , 18 , 19 ], mental health difficulties [ 20 ], and academic adjustment [ 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…Concerns about the prevalence of bullying are magnified by concerns about the adverse physical, social, and psychological effect on both the victims and perpetrators of bullying. There is evidence to show that bullying and victimization are strongly related to behavioral misconduct [ 13 , 14 ], poor physical health [ 15 , 16 ], psychosocial adjustment [ 17 , 18 , 19 ], mental health difficulties [ 20 ], and academic adjustment [ 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…Bullying during childhood and adolescence is a common experience that has potentially far reaching negative implications [1-3]. Bullying is a broad construct that is manifested by deliberate antagonistic behavior by the bully towards the victim, persistence of this behavior over a period of time, and an imbalance of power between the bully and the victim [4-8].…”
Section: Introductionmentioning
confidence: 99%
“…The present finding that dissociation predicts peer problems indirectly supports Mori's (2018) finding that dissociation predicts loneliness in school. However, for example, Sesar et al (2012) suggested that exposure to bullying tends to be associated with higher dissociation. Yamasaki et al (2016) also suggested that peer victimization may contribute to an increase in dissociation.…”
Section: Discussionmentioning
confidence: 99%
“…Understanding how dissociation overlaps with emotional and behavioral difficulties may provide clues to prevent the exacerbation of maladjustment. Several studies have reported that past peer relationship problems, such as bullying, are associated with high levels of dissociation (Sesar, Bariši c, Pandža, & Dodaj, 2012;Yamasaki et al, 2016). One study reported that A-DES scores predicted perceived loneliness in school, based on a panel survey conducted over a year and a half among a community sample of adolescents aged 12-16 years (Mori, 2018).…”
mentioning
confidence: 99%